Anticorpos contra sarampo e rubéola em crianças portadoras de Leucemia Linfóide Aguda - Alcanfôr, Brasília Mendes de Melo (2009)
The Acute Linfoid Leukemias (ALL) represent one third of oncologic disease in childhood. Children, at the end of treatment, can present endangerment of immune response, secondary to the illness itself and the chemotherapy, so that it is important the evaluation of humoral immunity against vaccine antigens, with the purpose to establish suitable vaccination protocols. Despite being controlled by vaccination, there are registers of imported cases of measles in Brazil, originating of Europe and Asia, with risk of re-introduction of the illness, as well as recent outbreak of rubella in brazilian territory. With the objective to evaluate the persistence of the protection against measles and rubella in children with ALL previously immunized, as well as the response to one dose of reinforcement vaccine after the end of the chemotherapy, it was realized an study of transversal cut in patients with younger than 19 years, assisted by a service of Pediatric Oncology of reference in state of Sergipe. It was studied 83 patients carriers of ALL, of both genders, of which 30 were on chemotherapy treatment (maintenance phase), 29 had ended the treatment, presented hematologic recuperation, but had received any additional vaccine dose yet, and 24 had concluded the treatment and received a reinforcement dose of vaccine MMR there were at least 4 weeks. There were either evaluated 30 healthy children and with complete vaccination. Antibodies of IgG class against measles and rubella were dosed, considering protected those that present higher or equal values than 0,275 UI/mL and higher or equal than 10 UI/mL respectively for measles and rubella. Results showed that the minor frequency of patients protected against measles occurred at group of patients after the end of treatment and that had not received vaccine reforce (41,4%), while the highest frequency was in the group that received addicional dose (79,2%; p=0.005), similar percentage of the control group (73%; p=0,01). It was observed similar situation for rubella, but the difference was not statistically significant. Antibodies levels against measles and rubella of patients that ended the treatment and did not receive enforcement vaccination were significantly lower than the other 3 groups. For patients that ended the chemotherapy treatment for ALL the critic phase is immediately after the final of treatment, suggesting that patients are supposed to receive a dose of enforcement of the vaccine for measles and rubella as soon as highest hematologic recovery occurs. The vaccination enforcement dose seems to have been capable of re-activate the immunologic memory, suggesting that the same was not compromised for the illness or treatment.